Deadly betrayal [large type] - Clay, James (Clay, James. Rance Dehner westerns, 2025)
"Range Detective Rance Dehner is called to Grimsby, Arizona, where a man who once saved his life has been accused of murder. But the case presents far more danger than caging the real killer. Years before, as a young deputy sheriff in Grimsby, Rance made a misstep that cost the life of the woman he loved. The past flames into the present as old hatreds emerge. Rance must fight those who would kill him for past actions and those who want to stop his investigation. As Dehner shoots his way through a vicious web of deceit, he encounters a beautiful young Asian woman, a woman unfamiliar with American ways, who does not realize that she is at the center of a brutal struggle for power and wealth."--